Design and application of a new type of ventilator extension tube fixation device (一种新型呼吸机延长管固定装置的设计与应用) - QUAN Xiangrong (全相融); SUN Xiumei (孙秀梅); LI Jingwen (李静文) (中西医结合护理)
Mechanical ventilation is a commonly used treatment for critically ill patients. Ventilator-associated pneumonia (VAP) is a common and serious complication in patients with mechanical ventilation. Effective tupe fixation can prevent condensate reflux and reduce the occurrence of VAP. This study introduces the design and use method of a new type of ventilator extension tube fixation device, which can effectively improve the fixation function of ventilator extension tube, prevent condensate backflow, and increase the patient comfort. (机械通气是危重症患者常用的治疗手段, 呼吸机管路的维护和固定是预防相关并发症的重要护理措施。本研究介绍了一种新型呼吸机延长管固定装置的设计和使用方法, 其兼具灵活性和稳定性, 不仅能有效防止冷凝水的逆流, 而且提升了固定功能, 增加了患者的舒适性。)